Characterization of the Statistical Variability of Systolic and Diastolic Blood Pressure - Soueidan, Karen; Dajani, Hilmi R.; Bolic, Miodrag; Groza, Voicu; Chen, Silu (CMBES Proceedings, 2010)
Blood pressure is subject to significant physiological variability over time. The fluctuation of systolic and diastolic values (SBP and DBP) could lead to unrepresentative readings if not taken into consideration. This paper presents a statistical study of this variability and focuses on its main frequency components using continuous recordings of the arterial pulse waveform in healthy subjects and in ICU patients. Results show that very low frequencies between 0.025 and 0.05 Hz, low frequencies between 0.05 and 0.15 Hz, and high frequencies between 0.15 and 0.5 Hz are all important contributors to the variability. Moreover, the standard deviation of SBP and DBP values, combined with device errors, could result in readings that are associated with an unacceptable level of measurement uncertainty.